Islamic Education Among the Islamic Khmer Community in Kampuchea - Aminas, Ly; In’am, Akhsanul; Khozin, Khozin (Electronic Journal of Education, Social Economics and Technology, 2025)
This article is about islamic education in the khmer islamic community of cambodia. This study aims to examine the role of Islamic educators in sustaining and developing Islamic education among the Khmer Islam minority in Cambodia. Using a descriptive qualitative approach, data were collected through interviews, field observations, and document analysis. The findings reveal that Islamic educators play multiple roles as teachers, community leaders, and agents of social change. Despite limited infrastructure and minimal state support, they manage to run community-based education systems emphasizing Islamic values, morality, and cultural identity. The study highlights the importance of structural support and continuous empowerment of Islamic educators to ensure the sustainability of Islamic education in minority communities. This study concludes that Islamic education in the Khmer Islam community in Cambodia has a long history and an important role in maintaining the religious and cultural identity of the minority Muslim community there. Despite facing serious challenges such as limited Education Infrastructure, facilities, quality of teachers, an incomplete curriculum, and social and economic influences that limit access to education. However, with government support, international cooperation, curriculum development, and community empowerment, the prospects for Islamic education in this community are quite promising. Strengthening Islamic education that combines religious values with modern science and the active role of society is the key to the success of future Islamic education in Khmer Islamic society.